Akupunktur Medik untuk Program Penurunan Berat Badan - Indah Dian Shafira (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction Obesity is an abnormal condition in which fat tissue accumulates that can lead to health problems. Method a literature review study, in which researchers search, combine sari cores and analyze facts from several scientific sources that are accurate and valid. Results showed that acupuncture can lose weight by mechanisms of regulates the endocrine system, improve the digestive system, lowers oxidative stress, suppresses appetite, and increase lipolytic activity. Conclusion acupuncture is used as one of the effective alternative methods for weight loss.